PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DEPARTEMEN DIAPHRAGM PADA PT XYZ KOTA DEPOK - Mawar Irawanti; Eigis Yani Pramularso; Hardani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
Human resources play a crucial role in a company, enabling it to grow effectively and operate as expected. This can be achieved through a competent workforce, optimal employee performance, and a supportive work environment characterized by strong work discipline. This study aims to identify the impact of work discipline and the work environment on employee performance in the diaphragm department at PT XYZ. The sample used was a saturated sample, where the entire employee population 41 people was included. The data analysis method employed was multiple linear regression, and data collection was conducted via a questionnaire. Partially, work discipline has a significant positive effect on employee performance, and partially, employee performance is also positively and significantly influenced by the work environment. The F-test yielded a p-value of 0.000, indicating that work discipline and the work environment together have a significant positive effect on employee performance.